Beef consumption and fatty acids serum concentration: relationship with salivary gland tumors in Córdoba, Argentina - Cittadini, María C.; Cornaglia, Paola M.; Perovic, Nilda R.; Joekes, Silvia; Heinze, Verónica M.; Bernal, Claudio; Actis, Adriana Beatriz (2022)
Fil: Cittadini, María C. Universidad Nacional de Córdoba. Facultad de Ciencias Médicas. Escuela de Nutrición; Argentina.